2020
DOI: 10.1002/edm2.209
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the beneficial effect of aliskiren in attenuating neuropathic pain in diabetic Sprague‐Dawley rats

Abstract: Objectives Worldwide, diabetic neuropathy (DN) is a major complication of diabetes mellitus. The direct renin inhibitor aliskiren is recognized as a treatment for cardiovascular disease in diabetic patients, but little is known about its potential benefits in cases of diabetic neuropathy. Accordingly, we investigated the effects of aliskiren (ALIS) and gliclazide (GLZ) and their combination therapy on peripheral neuropathy in streptozotocin‐induced diabetic rats. Methods In total, 112 adult Sprague‐Dawley rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In our clinical study, the number of T2DM patients receiving aliskiren, a renin inhibitor, was quite limited, so that the effect of aliskiren on DPN development could not be analyzed. Nonetheless, it is to be noted that an animal study demonstrated the beneficial effect of aliskiren in attenuating DPN in streptozotocin-induced diabetic rats 46 . Considering the significant impact of β-blockers on DPN development in the clinical study (see Table 2 ), the peripheral β-adrenoceptor/renin/Ang/AT 1 receptor system appears to participate in DPN development accompanying T2DM, and may serve as therapeutic targets for DPN.…”
Section: Discussionmentioning
confidence: 99%
“…In our clinical study, the number of T2DM patients receiving aliskiren, a renin inhibitor, was quite limited, so that the effect of aliskiren on DPN development could not be analyzed. Nonetheless, it is to be noted that an animal study demonstrated the beneficial effect of aliskiren in attenuating DPN in streptozotocin-induced diabetic rats 46 . Considering the significant impact of β-blockers on DPN development in the clinical study (see Table 2 ), the peripheral β-adrenoceptor/renin/Ang/AT 1 receptor system appears to participate in DPN development accompanying T2DM, and may serve as therapeutic targets for DPN.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable preclinical data has shown that RAS inhibitors, such as angiotensinconverting enzyme inhibitors (ACEi) and angiotensin receptor blockers (ARB), exert a neuroprotective effect in various murine models of peripheral neuropathy [4,5], such as traumatic [6][7][8], diabetic [9][10][11] and toxin-induced neuropathies [12]. A beneficial effect of ramipril, an ACEi, was demonstrated in animal models of chronic constriction injury, streptozotocin-induced diabetes, and oxaliplatin-induced acute pain syndrome [6,11,13]. Recently, Kim et al reported that preventive or curative treatment with losartan, an ARB, delayed the onset of mechanical allodynia induced by PTX in rats [14].…”
Section: Introductionmentioning
confidence: 99%
“…The ineffectiveness of medical interventions arises partly due to the poorly understood molecular mechanism of neuropathic pain. Both peripheral and central sensitization are known to be implicated in the pathogenesis of neuropathic pain 23‐25 . Whereas the anomalous excitability of the primary sensory neurons during peripheral sensitization may be due to maladaptive changes in the gene transcription and translation of enzymes, receptors, and voltage‐dependent ion channels in the dorsal root ganglion, neuroinflammation caused by pathological microglia activation takes a major part in the process of central sensitization 26‐29 .…”
Section: Introductionmentioning
confidence: 99%
“…Both peripheral and central sensitization are known to be implicated in the pathogenesis of neuropathic pain. 23 , 24 , 25 Whereas the anomalous excitability of the primary sensory neurons during peripheral sensitization may be due to maladaptive changes in the gene transcription and translation of enzymes, receptors, and voltage‐dependent ion channels in the dorsal root ganglion, neuroinflammation caused by pathological microglia activation takes a major part in the process of central sensitization. 26 , 27 , 28 , 29 However, how the deranged molecular pathways underlying peripheral and central sensitization could be targeted therapeutically is still an active area of investigation.…”
Section: Introductionmentioning
confidence: 99%